Response surface optimisation of high antioxidant jelly from Musa paradisiaca and Trigona sp. honey using central composite design as a convenient functional food - Anuar, Mohd Nur Nasyriq; Ibrahim, Muhammad; Kharsa, Badr Eddin; Mat Alewi, Nur Aizura; Hazali, Norazlanshah; Ibrahim, Muhammad; Kaderi, Mohd Arifin; Md Isa, Muhammad Lokman (Universiti Putra Malaysia, 2019)
The optimum combination of Musa paradisiaca (MP) and Trigona sp. Honey (TH) in formulating high antioxidant jelly was analysed for total carbohydrate content (CHO), antioxidant capacity (AC), and acceptability via the Response Surface Methodology. Central composite design was employed to optimise the combination effect of two independent variables; namely MP (X1: 20-100%) and TH (X2: 20-100%) on the recovery of three responses; total carbohydrate content (Y1), antioxidant capacity (Y2), and acceptability (Y3). A polynomial model generated a satisfactory fitting of the experimental data with regards to total carbohydrate content (R2 = 0.8974, p < 0.0024), total antioxidant capacity (R2 = 0.9702, p < 0.0001), and acceptability (R2 = 0.9136, p < 0.0001). The optimum combination for maximum recovery of CHO, AC and acceptability were 20% of MP and 20% of TBH, with a predicted CHO of 33 Kcal/5 g, AC of 0.34 nm and acceptability score of 6.16 (< 5: not accepted; > 5: accepted).